Female urinary incontinence: quality of life comparison on reproductive age and postmenopausal period - Mariana Tirolli Rett; Érica Brito Wardini; Josimari Melo de Santana; Andreza Carvalho Rabelo Mendonça; Aline Teixeira Alves; Cristina Said Saleme
Abstract Introduction: urinary incontinence (UI) is defined as any involuntary leakage of urine and their symptoms can affect women's quality of life (QoL). Objectives: to compare incontinent women's QoLin reproductive age (G1) with those in post menopausal period(G2). Material and methods: a descriptive and retrospective study involved 86 women with UI complaints. Clinical, sociodemographic, obstetrical and gynecological antecedents were collected. Pelvic floor evaluation was conducted by digital palpation and QoL was evaluated by King's Health Questionnaire (KHQ). Mann-Whitney and t Student test were used to compare QoL domains. Results: 36 women in reproductive age (G1) 42.9 (± 7,4) years and 50 women in postmenopausal period (G2) 61,6 (± 9,3) years were assessed. The G2 showed significantly more nocturia (p = 0,0057), urge incontinence (p = 0,0061) and enuresis (0,0021) symptoms, whereas in G1 bladder pain and voiding difficulties were more significant. KHQ domains showed statistical differences in: general health perception (G1 26,4 ± 16,8 versus G2 38,0 ± 16.2; p = 0,0019) and emotions (G1 15,1 ± 31,3 versus G2 38,9 ± 37,5; p = 0,0051). Conclusion: UI affects negatively QoLin women. Women on postmenopausal period showed higher impact on the QoLdomains related to general health perception and emotions.